Carbon dioxide capture using amine functionalized silica gel - Sakpal, Tushar; Kumar, Asheesh; Kamble, Sanjay; Kumar, Rajnish (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
Commercially available silica gel is chemically modified for carbon dioxide capture. Calcinated silica gel of certain particle size functionalized with amine using two different methods, wet impregnation and grafting via silane chemistry has been employed as a porous media. The prepared material is characterized by Fourier transform infrared, scanning electron microscopy, energy dispersive analysis of X-rays, thermogravimetry and N-2 physisorption techniques. Gas uptake measurements have been carried out to ascertain the CO2 capture capacity of the amine functionalized material. The experiments have been carried out at moderate pressure and temperature range to ascertain its potential for easy scale up.
Keywords: Amine functionalized silica gel; Carbon dioxide capture; grafting; Poly(ethyleneimine); Silane chemistry; Wet impregnation